Enhanced photocatalytic performance of visible-light active graphene-WO3 nanostructures for hydrogen production. (September 2018) - Tahir, Muhammad Bilal; Nabi, Ghulam; Khalid, N.R.
Abstract: In this article, visible light driven graphene-WO3 (WG) photocatalysts have been synthesized through facile hydrothermal process for H2 evolution through water splitting under visible light illumination. For comparison, neodymium-WO3 nanostructure was also prepared. The as-synthesized composites were characterized by XRD, SEM, BET, EDX, XPS, UV–vis absorption spectra and Photoluminescence (PL) emission spectroscopy. Experimental results showed that WG-7 composite (7% graphene content into WO3 ) had excellent photocatalytic performance (rate of H2 evolution 288/µmol h −1 g −1 ) towards hydrogen production when compared to pristine WO3 . It was also confirmed by optical analysis that incorporation of graphene into WO3 and Nd-WO3 photocatalysts prevented the electron-hole recombination and boosts the reduction reactions for H2 evolution. PL emission spectra confirmed the effective charge-separation in graphene incorporated WO3 composite. It was demonstrated that photocatalytic activity for hydrogen production increases with increasing doping content of graphene upto 7 at%. However, further increase in incorporated content above optimal level has decreased the photocatalytic performance of the composite. The enhanced photocatalytic activity of WG composites could be attributed to extended visible light absorption, high surface area and efficient charge-separation due to synergistic effects between graphene and WO3 . This study gives a new perspective on the fabrication of novel photocatalyst for environmental and energy applications.